2003
DOI: 10.1089/089771503767869980
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression in Response to Brain Injury: Enhanced Expression and Alternative Splicing of Rat Prosaposin (SGP-1) mRNA in Injured Brain

Abstract: Prosaposin, the precursor of saposins or saps, is an injury-repair protein that acts on both neurons and glia. Previous studies identified the prosaposin gene as one of differentially expressed genes following nerve injury. In the present study, we investigated expression of prosaposin mRNA in injured brain utilizing rat models of focal cerebral ischemia and cortical stab wound in order to explore the significance of prosaposin in nerve injury. In ischemic brain, the level of prosaposin mRNA was elevated great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
2
29
0
2
Order By: Relevance
“…Similarly, total levels of prosaposin mRNA and protein are increased following nerve injury in motoneurons, beginning on the third day following injury and continuing to change until post-injury day 21 (Chen et al, 2008; Unuma et al, 2005). Furthermore, prosaposin expression and release are greatly upregulated in animal models of focal cerebral ischemia (Costain et al, 2010; Hiraiwa et al, 2003; Yokota et al, 2001), and prosaposin release from the retinal pigment epithelial cells in the eye can be elevated by cell stress induced by either light or hydrogen peroxide (Toyofuku et al, 2012). …”
Section: Prosaposin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, total levels of prosaposin mRNA and protein are increased following nerve injury in motoneurons, beginning on the third day following injury and continuing to change until post-injury day 21 (Chen et al, 2008; Unuma et al, 2005). Furthermore, prosaposin expression and release are greatly upregulated in animal models of focal cerebral ischemia (Costain et al, 2010; Hiraiwa et al, 2003; Yokota et al, 2001), and prosaposin release from the retinal pigment epithelial cells in the eye can be elevated by cell stress induced by either light or hydrogen peroxide (Toyofuku et al, 2012). …”
Section: Prosaposin Releasementioning
confidence: 99%
“…Given the aforementioned studies demonstrating that prosaposin expression and release are enhanced following ischemia (Costain et al, 2010; Hiraiwa et al, 2003; Yokota et al, 2001), a number of groups have explored the possibility that prosaposin might protect cells from ischemic damage. For example, the infusion of prosaposin into the lateral ventricles of gerbils prior to the induction of ischemia was found to prevent learning disabilities resulting from ischemic damage (Sano et al, 1994).…”
Section: Effects Of Secreted Prosaposin In the Nervous Systemmentioning
confidence: 99%
“…The prosaposin gene contains 15 exons that can be transcribed into several mRNAs, resulting from alternative splicing of the 9-bp exon 8 [136,137]. A splicing variant of prosaposin without exon 8 is preferentially expressed in the brain following injury [138], and alternative splicing of the prosaposin gene was assumed to be the mechanism responsible for differential sorting of the different prosaposin forms [139].…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Amentioning
confidence: 99%
“…Donner et al 53 reported that at least 2 of 19 variants in the prosaposin (PSAP) gene in the 10q22.1 region showed a strong allelic association with PD, but not with other anxiety disorders, such as GAD, social anxiety disorder, agoraphobia, or other phobias. PSAP may function as a neurotrophic factor 63 or a neural injury-repair protein; 64 but its specific role in the development of PD requires further analysis. Notably, anxious mice showed increased expression of PSAP in the brain periaqueductal gray (PAG), 55 a region with a putative role in panicogenesis.…”
Section: Chromosome 10mentioning
confidence: 99%